2020
DOI: 10.1044/2019_jslhr-19-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Deep Brain Stimulation on Speech Intelligibility in Persons With Essential Tremor

Abstract: Purpose The aim of this study was to investigate how deep brain stimulation (DBS) of the caudal zona incerta (cZi) affects speech intelligibility in persons with essential tremor. Method Thirty-five participants were evaluated: off stimulation, on chronic stimulation optimized to alleviate tremor, and during unilateral stimulation at increasing amplitude levels. At each stimulation condition, the participants read 10 unique nonsense sentences from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…2 Speech side effects were more frequent after left-sided lesions than after right-sided ones. Recent studies even considered the replacement of Vim by zona incerta as the target for DBS for ET 53,54 to reduce speech side effects.…”
Section: Discussionmentioning
confidence: 99%
“…2 Speech side effects were more frequent after left-sided lesions than after right-sided ones. Recent studies even considered the replacement of Vim by zona incerta as the target for DBS for ET 53,54 to reduce speech side effects.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the regions of the brain where optical fibers are implanted are different from the regions where electrodes are implanted in the DBS procedure. In DBS, electrodes are usually implanted into the globus pallidus internus to improve the motor function [54] or into the subthalamic nucleus [55] or the caudal zona incerta to improve tremor [56]. The optical fibers in PD animal models have been implanted into the mid-brain, with the goal of delivering the light as close as possible to the SNc, to preserve the dopamine producing neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The cZi is a small nucleus targeted in-between the red nucleus (Rn) and the posterior tip of the STN (pSTN) at the depth where the Rn has its maximal diameter (see Figure 1; Blomstedt, 2018), and this has been the DBS target of choice for ET at Umeå University Hospital since 2004. Previous investigations into the effects of DBS in the cZi have shown that unilateral cZi DBS can have a positive effect on voice tremor (Sandström et al, 2019b(Sandström et al, , 2018, also in the long term (Sandström et al, 2019a), and that habitual cZi DBS, optimized to treat the motor symptoms of ET, does not affect speech intelligibility (Sandström et al, 2020). However, in the same clinical population, it was also noted that speech intelligibility might deteriorate during highamplitude stimulation from electrode contacts higher up in the PSA (Sandström et al, 2020) and that successful voice tremor management may depend on the exact location of the electrode within the cZi (Sandström et al, 2019b); results that indicate that speech and voice outcomes could vary depending on targeting precision.…”
mentioning
confidence: 99%